Hedge Funds or Mutual Funds, What proves Significant in the Long run? An Empirical Study - Jani, Vibhuti (2008)
The objective of this research paper is to measure the performance of hedge fund and mutual fund and to indicate the similarities and differences between them. The trading strategies followed by hedge funds are convertible arbitrage, distressed securities, emerging markets, growth fund, macro or global, market neutral along with tactical trading and market speculating and the strategies used by mutual fund are momentum trading and contagion trading strategies and investment style based on the benchmark of broad markets which are very divergent but are believed to be soon converging with hedge fund trading strategies. Few papers which have a thorough in-depth details and analysis on the topic have been studied and analyzed and a conclusion is provided to have a better understanding about the issue. The paper analyses the present Hedge fund and Mutual fund data with the help of various graphs and charts.